(untitled) (Praxis Educativa, 2023)
This summary discusses the results of a research that aimed to investigate the possible relationships between the life trajectories of beginning Physical Education (PE) teachers, training processes and the challenges of starting to teach. The study starts from the premise that life stories constitute a reservoir of knowledge that beginning teachers would mobilize in situations of facing the challenges and dilemmas of starting to teach. The study was carried out with 12 PE teachers who had graduated from the PE degree course at the Federal University of Minas Gerais (UFMG) and used a single instrument for data construction: the narrative interview. The research findings suggest that life trajectories shape plural teachers, with different social dispositions, which would make professional insertion trajectories a plural, situated and non-transferable social phenomenon.